2017
DOI: 10.1080/21645515.2017.1313940
|View full text |Cite
|
Sign up to set email alerts
|

Meningococcal serogroup B vaccine: Knowledge and acceptability among parents in Italy

Abstract: This study aimed to evaluate the knowledge and attitudes about Meningococcal meningitis B and the relative vaccine for children among a sample of parents in Italy. A cross-sectional investigation was conducted from October to December 2015 among a sample of 910 parents in the geographic area of Naples and Salerno (Italy). In total, 543 of 910 parents returned a completed questionnaire for a response rate of 59.7%. Almost all parents had heard about meningitis (95.8%), 79.8% of these knew the mode of transmissi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
52
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(65 citation statements)
references
References 26 publications
(33 reference statements)
13
52
0
Order By: Relevance
“…The first of these aspects, likely to be the most important, relates to the low immunization rates registered in most of the Italian Regions in the period 2014–2016. Vaccine hesitancy is regarded as one of the leading causes of the decline in vaccination coverage in recent years [ 29 – 36 ]. To address this issue, in June 2017 the Italian parliament approved the decree-law no.…”
Section: Discussionmentioning
confidence: 99%
“…The first of these aspects, likely to be the most important, relates to the low immunization rates registered in most of the Italian Regions in the period 2014–2016. Vaccine hesitancy is regarded as one of the leading causes of the decline in vaccination coverage in recent years [ 29 – 36 ]. To address this issue, in June 2017 the Italian parliament approved the decree-law no.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 It is well recognised that vaccine uptake may be greatly influenced by multiple factors such as, for example, lack of recommendation by general practitioners, concerns about vaccination effectiveness and safety, lack of knowledge and information, low perception of risk, difficult access to preventive activities, and socio-economic predictors. [5][6][7][8][9][10] Among the userrelated determinants affecting decisions about whether to vaccinate, parents' vaccine hesitancy represents a recent and growing concern in developed and developing countries. 11 It is well known that vaccine hesitancy refers to all kind of concerns that parents express by refusing some vaccines, delaying vaccines or accepting others, but they are unsure of doing so, despite availability of services and it is complex and context specific, varying across time, place, and vaccines.…”
Section: Introductionmentioning
confidence: 99%
“…11 It is well known that vaccine hesitancy refers to all kind of concerns that parents express by refusing some vaccines, delaying vaccines or accepting others, but they are unsure of doing so, despite availability of services and it is complex and context specific, varying across time, place, and vaccines. [11][12][13] Moreover, it is important to understand that primary care providers and parental knowledge of and attitudes towards both the efficacy and safety of vaccines may have an effect on the decision of vaccinating the children 8,[14][15][16][17] and the primary care providers play a crucial role in promoting prevention and education interventions to achieve high immunization rates. For this reason, it is vitally important to improve acceptance and trust of parents in vaccinations by studying the phenomenon of vaccine hesitancy and understanding why they delay or refuse to vaccinate their children for the purposes of an effective vaccination planning.…”
Section: Introductionmentioning
confidence: 99%
“…The parents participating in this study showed a positive attitude towards vaccination in general, as demonstrated by the high rate of immunisation against MMR, meningococcus C, varicella and HPV that were higher than the national and regional averages. 13 , 14 , 15 , 16 , 17 HPV coverage was higher than that. The most frequent time interval between the first and second dose of MenB vaccine was 3–6 months (up to seven months in some cases), and about 47% of the newborns were not immunised within the recommended .…”
Section: Discussionmentioning
confidence: 76%
“…Mothers with a university education were well represented in both groups, which contrasts with the finding of Mameli 26 and Anello 27 that a willingness to have children vaccinated inversely correlates with their parents’ educational level but is in line with those of Morrone . 15 Comparison of the adverse effects reported by the parents showed that the children in group B significantly more frequently experienced pain with functional impotence and pain at the inoculation site, whereas those in group A more frequently experienced mild general reactions such as restlessness, fever, headache and diarrhea. These findings are in line with those of many studies of MenB 21 , 28 , 29 and other vaccinations 30-32 and indicate that the onset of adverse events is age related.…”
Section: Discussionmentioning
confidence: 99%